Prognostic value of the ascites characteristics in pseudomyxoma peritonei originating from the appendix - Wang, Bing; Sun, Xibo; Ma, Ruiqing; Yang, Zhenpeng; Tang, Huazhen; Lu, Shuai; Qu, Jinxiu; Wang, Yuying; Rao, Benqiang; Xu, Hongbin (Frontiers in Surgery, 2023)
Backgrounds: Pseudomyxoma peritonei (PMP) is a rare disease, which is influenced by many factors with the overall survival (OS). To date, no ascites characteristics have been reported to predict OS for patients with PMP. The present study therefore aimed to describe the ascites characteristics for PMP and identify prognostic factors for survival. Methods: Between June 2010 and June 2020, 473 PMP patients who underwent cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) were included in a retrospective study. Survival analysis was performed with the Kaplan-Meier method by the log-rank test, and a Cox proportional hazards model. Associations between categorical variables were analyzed using the chi-square test. Results: Among the all included patients, there were 61% were female. The median OS was 47 months (range, 4 to 124 months) at the last follow-up in December 2020. Ascites characteristics can be divided into light blood ascites, “Jelly” mucus ascites and faint yellow and clear ascites. Multivariate Cox analysis showed that degree of radical surgery, ascites characteristics and pathological grade were independently associated with OS in PMP patients. Chi-square test documented that faint yellow “Jelly” ascites was related to low-grade PMP and light blood ascites was associated with high-grade PMP (P < 0.01). Conclusions: Light blood ascites, incomplete cytoreduction surgery and high-grade histopathology may predict poor OS in appendix-derived PMP.